2009
DOI: 10.1080/01443410903310674
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distributed questioning with varied examples on exam performance on inference questions

Abstract: The purpose of this study was to investigate whether the distributed presentation of different versions of a question would produce better performance on a new version of the question than distributed presentation of the same version of the question. A total of 48 four question sets of five alternative multiple-choice questions were presented during a college lecture course. The answers to all the four questions in each set required an inference from the same fact statement. One question in each set appeared o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Experiment 2 convincingly counters this possibility, in part because the baseline levels (no quiz) for the application and definition‐response exam items are comparable (Figure ). We suggest that quizzing might benefit transfer even more robustly by varying the contexts used across the three application quizzes so that the target concept/principle is more broadly and completely illustrated (see Glass, , for a related finding). We note that it is possible that requiring middle‐school students to repeatedly study applications might produce transfer effects similar to those found here for the application quiz items.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Experiment 2 convincingly counters this possibility, in part because the baseline levels (no quiz) for the application and definition‐response exam items are comparable (Figure ). We suggest that quizzing might benefit transfer even more robustly by varying the contexts used across the three application quizzes so that the target concept/principle is more broadly and completely illustrated (see Glass, , for a related finding). We note that it is possible that requiring middle‐school students to repeatedly study applications might produce transfer effects similar to those found here for the application quiz items.…”
Section: Discussionmentioning
confidence: 92%
“…The theoretical idea is that the application quiz question forces students to consider the implications of the principle and how it is instantiated, thereby supporting the generation of inferences (or abstraction) required by the exam question (in line with the transfer‐appropriate processing principle from the memory literature; McDaniel, Friedman, & Bourne, ; Morris, Bransford, & Franks, ; Roediger, Weldon, & Challis, ). Preliminary support for this idea is a recent finding showing quiz‐related gains on inference exam questions in a college class (Glass, ).…”
Section: Methodsmentioning
confidence: 90%
“…Requiring students to answer a question reduces the effect of divided attention on retention compared with a similar condition without question-answering (Mulligan & Picklesimer, 2016). Furthermore, answering the question increases long-term retention of the answer and the testing effect alone causes a meaningful increase in classroom performance (Glass, 2009;Roediger, Agarwal, McDaniel, & McDermott, 2011). If a question had not followed the presentation of the fact statement, but merely passive listening was required, then there would have been a much greater reduction in retention of the content being presented.…”
Section: The Severity Of the Effect Of Classroom Divided Attention Onmentioning
confidence: 99%
“…Both online and clicker quizzes are generally easily implemented, although a possible disadvantage is that they may be less potent than more extensive formats (Rowland, 2014). Both methods have been investigated in the classroom in relatively few studies to date (e.g., McDaniel et al , 2007; Glass, 2009; Mayer et al , 2009; Anderson et al , 2011).…”
Section: Introductionmentioning
confidence: 99%